Hubungan Mekanisme Koping Dengan Kualitas Hidup Pasien Gagal Ginjal Kronik yang Menjalani Hemodialisis di Rumah Sakit Santa Elisabeth Medan - Meiling Siahaan; Rosminta Girsang; Ade Pryta Simaremare (Nommensen Journal of Medicine, 2020)
Background: Chronic kidney failure is a state of progressive, irreversible destruction of kidney structure that requires permanent kidney replacement therapy. Global prevalence is 11.7% -15.1%. Chronic disease conditions and prolonged treatment can affect the patient's mental health and quality of life. The process by which a person attains physical and mental readiness in dealing with stressful situations is called coping. Quality of life is an individual's perception of their position in life. The aim of this study was to determine the relationship between coping mechanisms and quality of life in patients with chronic renal failure undergoing hemodialysis. Method: This research was analytical correlative with cross sectional research design. Sampling with consecutive sampling technique and obtained as many as 35 respondents. The criteria for patients in this study were patients diagnosed with chronic renal failure and undergoing hemodialysis with an age limit of 18 - 65 years, compos mentis awareness status and willingness to become respondents. The study was conducted in November 2019- January 2020. Patient data were obtained through medical records and questionnaires kidney disease quality of life short form (KDQOL-SF) and a brief cope scale. Results: The results of statistical tests obtained p value = 0.007 and r = 0.413 (p <0.05; r> 0.05). These results indicate that there is a relationship between coping mechanisms and quality of life in patients with chronic renal failure undergoing hemodialysis. More male respondents than women with 56-65 years age group, the highest education status is college; working as a civil servant, long undergoing HD 1-12 months. Based on statistical analysis it is known that the coping mechanism of poor respondents (57.1%), poor quality of life (54.3%). Conclusion: There was significant relationship between coping mechanisms with the quality of life of patients with chronic renal failure undergoing hemodialysis with moderate correlation strength and positive direction.